The Role of Translation in Foreign Language Teaching - Frasheri, Alba; Hyso, Ardiana (Richtmann Publishing, 2012)
In this article has been treated the importance of the translation in foreign language teaching. At first, it has been treated by acomparative point of view the difference between the Professional Translation and the Pedagogic Translation. This difference isessential because their objective is not the same. The Professional Translation communicates the same message between the sourcetext and the target text, while the Pedagogic Translation’s purpose is to teach a foreign language. Our students must continuouslycompare the foreign language (French, English, Italian etc.) to Albanian. Although our students do not intend to enter the translationprofession, for them translating helps relate L1 to L2: a mental process takes place in their minds on an unconscious level, every timethey speak the other language. The special examples illustrate the role of the translation in the teaching of the foreign languages by thelexical and syntactical structure exercises. Despite it is not always involved in the new methods of the foreign languages, translation canbe a useful tool and an effective method to learn a language.